The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1002/mabi.201500435
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study of Cellular Uptake and Subcellular Localization of Doxorubicin Loaded in Self‐Assemblies of Amphiphilic Copolymers with Pendant Dendron by MDA‐MB‐231 Human Breast Cancer Cells

Abstract: Previously synthesized amphiphilic diblock copolymers with pendant dendron moieties have been investigated for their potential use as drug carriers to improve the delivery of an anticancer drug to human breast cancer cells. Diblock copolymer (P71 D3 )-based micelles effectively encapsulate the doxorubicin (DOX) with a high drug-loading capacity (≈95%, 104 DOX molecules per micelle), which is approximately double the amount of drug loaded into the diblock copolymer (P296 D1 ) vesicles. DOX released from the res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 51 publications
1
3
0
Order By: Relevance
“…30 In plasma at pH 7.4, both S@C-PLGA NPs and S@PLGA NPs exhibited similar drug release patterns, where ~12% of Stattic was released rapidly within 2 h. This indicated rapid diffusion of Stattic from the polymeric matrix to the plasma protein, likely owing to affinity of Stattic towards albumin molecules. 31 A similar observation has been reported previously, where Stattic entrapped within a synthetic polymeric micellar carrier (P71D3) 32 was rapidly released when the drug-carriercomplexes were incubated in an albumin solution. 33 The Stattic burst release from S@C-PLGA NPs in this study was considerably low (< 15%), suggesting the suitability of C-PLGA NPs as the delivery vehicles for Stattic and antimetastatic drugs with a similar chemical structure.…”
Section: Stattic Releasing Profile In Pbs and Plasmasupporting
confidence: 83%
“…30 In plasma at pH 7.4, both S@C-PLGA NPs and S@PLGA NPs exhibited similar drug release patterns, where ~12% of Stattic was released rapidly within 2 h. This indicated rapid diffusion of Stattic from the polymeric matrix to the plasma protein, likely owing to affinity of Stattic towards albumin molecules. 31 A similar observation has been reported previously, where Stattic entrapped within a synthetic polymeric micellar carrier (P71D3) 32 was rapidly released when the drug-carriercomplexes were incubated in an albumin solution. 33 The Stattic burst release from S@C-PLGA NPs in this study was considerably low (< 15%), suggesting the suitability of C-PLGA NPs as the delivery vehicles for Stattic and antimetastatic drugs with a similar chemical structure.…”
Section: Stattic Releasing Profile In Pbs and Plasmasupporting
confidence: 83%
“…This observation is supported by another study wherein enhanced uptake of DOX was observed when loaded in dextran and poly(D,L-lactide- co -glycolide) blocks copolymer polymeric micelles as compared to DOX alone in DOX-resistant human cholangiocarcinoma (HuCC-T1) cells (51). Viswanathan et al observed twofold enhancement in the DOX potency in MDA-MB-231 cells when loaded in di-block copolymer-based micelles (52). …”
Section: Discussionmentioning
confidence: 99%
“…The hydrophobic core of a micelle can sequester a high dose of a particular drug while also having slow release, meaning less frequent injections. Because of their high density of well-structured hydrophobic groups, the use of dendrons such as poly­(benzyl ether) in the core of a block copolymer micelle increases the loading capacity of doxorubicin (DOX) to nearly twice that of similar linear copolymer vesicles and increases DOX delivery to tumors in mice by 2–5-fold compared to free DOX . The same drug has also been loaded into micelles generated from more rapidly biodegradable PCL dendron–PEG block copolymers with an 18% higher loading capacity and a drug release time 45 days longer than similar linear block copolymers .…”
Section: Dendron Micelles In Cancer Drug Loading Transport Targeting ...mentioning
confidence: 99%